Modern Walking Robots: A Brief Overview - Lyashenko, Vyacheslav; Ahmad, M. Ayaz; Belova, Nataliya; Sotnik, Svitlana (International Journal of Recent Technology and Applied Science (IJORTAS), 2021)
In this review, we would like to present some of the most interesting modern designs of walking robots: bipedal, quadropedal, hexopedal, and octopods. Their advantages and disadvantages are highlighted. It has been determined that structures with eight or more limbs are ineffective due to high level of electricity consumption. The use of more than six number of legs does not give noticeable advantages in profile cross-country ability or maneuverability, however, it allows to reduce the forces and moments of inertia forces due to decrease in mode coefficient (ratio of time spent by propulsor in support to time of entire step), and, consequently, smoother leg movements in swing phase.